Tomasza Różyckiego krajobrazy z odzysku - Szczukowski, Dariusz (Przestrzenie Teorii, 2025)
In this article I analyze the motif of landscape in the poetry of Tomasz Różycki in the context of post-memory and geopoetics referring to the history of Eastern Europe. I am interested in the category of the poet undertaken by Różycki – the heir of the lost landscapes of his grandparents, marked by emptiness, the tension between the past and the present, between the known and the lost. I am particularly interested here in the poem Spalone mapy as a record of the affective experience of the landscape, which is an attempt to regain ties with a lost place and history of one’s ancestors.